WHEN NUMBERS DON’T ADD UP: DISCORDANT THYROID FUNCTION IN HIV INFECTION - Zainol, Muhammad Qyairil Anwar Che; Ismail, Shartiyah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Thyroid function test (TFT) abnormalities in retroviral disease (RVD) are well documented, ranging from isolated low fT4 levels to overt hypothyroidism. However, careful evaluation of TFTs is essential as it presents a diagnostic challenge. CASE This is a case of a 28-year-old male with hypertension and end-stage kidney disease on peritoneal dialysis. He was diagnosed with vertical transmission of HIV since childhood, and the viral load is suppressed by regular antiretroviral therapy; oral lamivudine 500 mg daily, oral efavirenz 600 mg daily, and oral abacavir 600 mg daily. He was referred for abnormal TFT: fT4 7.88 (9.01–19.05 pmol/L), TSH 1.99 (0.35–4.94 mIU/L). TFT was done for a pre-cadaveric renal transplant workup. Clinically, he is euthyroid without any palpable goiter. He denied consuming biotin-containing supplementation. The results of the serial TFT showed a similar pattern. The pituitary hormonal workup excludes a central cause. Total T4 was normal at 68.1 (66–181 nmol/L). TSH assay interference was subsequently evaluated. Of the three different analyzers used (Lab A, B, and C), Lab A analyzer displayed normal TFT results: TSH 1.93 (0.4–4 mIU/L), fT4 10.8 (10–26 pmol/L), while the other labs showed low fT4 and normal TSH. Macro-TSH, heterophile antibody, and rheumatoid factor interference run by Lab B were negative. CONCLUSION A low fT4 level combined with a normal TSH level may be affected by multiple factors, such as antiretroviral therapy (ART) and assay interference, as seen in this patient's case. Due to limited resources and testing capacity, the specific antibody or causative agent cannot be identified. It is essential to take the necessary actions to eliminate other causes for the discordant TFT results and to prevent unnecessary thyroxine replacement. For this patient, any future TFT testing should be conducted at Lab A to rule out any potential assay interference with upcoming samples, if needed.